Characterization and cost–benefit analysis of automated bioreactor‐expanded mesenchymal stem cells for clinical applications - Russell, Athena L.; Lefavor, Rebecca C.; Zubair, Abba C. (Transfusion (Philadelphia, Pa.), 2018)
BACKGROUND Expanding quantities of mesenchymal stem cells (MSCs) sufficient to treat large numbers of patients in cellular therapy and regenerative medicine clinical trials is an ongoing challenge for cell manufacturing facilities. STUDY DESIGN AND METHODS We evaluated options for scaling up large quantities of bone marrow–derived MSCs (BM‐MSCs) using methods that can be performed in compliance with Good Manufacturing Practices (GMP). We expanded BM‐MSCs from fresh marrow aspirate in αMEM supplemented with 5% human platelet lysate using both an automated cell expansion system (Quantum, Terumo BCT) and a manual flask‐based method using multilayer flasks. We compared MSCs expanded using both methods and assessed their differentiation to adipogenic and osteogenic tissue, capacity to suppress T‐cell proliferation, cytokines, and growth factor secretion profile and cost‐effectiveness of manufacturing enough BM‐MSCs to administer a single dose of 100 × 106 cells per subject in a clinical trial of 100 subjects. RESULTS We have established that large quantities of clinical‐grade BM‐MSCs manufactured with an automated hollow‐fiber bioreactor were phenotypically (CD73, CD90, CD105) and functionally (adipogenic and osteogenic differentiation and cytokine and growth factor secretion) similar to manually expanded BM‐MSCs. In addition, MSC manufacturing costs significantly less and required less time and effort when using the Quantum automated cell expansion system over the manual multilayer flasks method. CONCLUSION MSCs manufactured by an automated bioreactor are physically and functionally equivalent to the MSCs manufactured by the manual flask method and have met the standards required for clinical application.